Oncological perineal massage in vaginal stenosis and dyspareunia in women with gynecological cancer: a randomized controlled trial - Pérez-García, Raquel; Abuín-Porras, Vanesa; Mínguez-Esteban, Isabel; Pecos-Martín, Daniel (Frontiers in Oncology, 2025)
BackgroundDyspareunia and vaginal stenosis are common complications in gynecological cancer survivors. Despite the widespread use of passive vaginal dilator therapy, physiotherapy interventions like oncological perineal massage (MPO®) have not been thoroughly evaluated.ObjectiveTis study aims to compare the effectiveness of MPO® perineal massage versus standard passive vaginal dilator therapy in managing dyspareunia, vaginal stenosis, sexual function, and quality of life in women with gynecological cancer.MethodsA randomized controlled trial involving 35 women (MPO® group: n = 18; control group: n=17) was conducted. The participants underwent either MPO® massage or passive dilator therapy for 10 weeks, with assessments at baseline (T0), mid-treatment (T1), post-treatment (T2), and 6-month follow-up (T3). Outcomes included pain (VAS), vaginal stenosis (CTCAE 5.0), sexual function (FSM-2), and quality of life (EORTC QLQ-C30).ResultsThe MPO® group demonstrated significantly greater reductions in vaginal pain (median VAS: 8.5 at T0 to 0 at T3, p<0.001), with improvements also seen in vaginal stenosis (absence/presence at T3: 16/2 vs. 3/14 in controls, p<0.001), sexual function (notably lubrication, penetration ease, and satisfaction), and quality of life (QLQ-C30 median score: 32.5 at T0 to 30 at T3 in MPO® vs. 35 to 32 in controls, p<0.001).ConclusionOncological perineal massage (MPO®) significantly improved pain, vaginal stenosis, sexual function, and quality of life in gynecological cancer survivors compared to passive dilator therapy. These findings support incorporating manual therapy techniques in comprehensive survivorship care in this population.Clinical Trial RegistrationClinicalTrials [https://clinicaltrials.gov/study/NCT06432998], identifier NCT06432998.